Conducta obstétrica en primigesta de 40 años con embarazo de 29.5 semanas más Covid 19. - Chernes Viejò, Teresa Marisol (2021)
SARS-CoV-2 is a type of coronavirus that causes the disease called COVID-19; this disease declared a pandemic by the WHO is responsible for countless deaths worldwide. According to scientific studies based on COVID 19 and pregnancy, the pregnant woman is exposed to being infected very easily due to the different changes that she experiences at this stage. For this reason they should be considered as a risk group. Covid - 19 in pregnancy takes special care due to the fact that two lives are at risk. It has not yet been demonstrated whether there is vertical transmission contagion, but whether horizontal transmission contagion has been evidenced during lactation. A case of a 40-year-old primigravida with a 29.5-week gestation pregnancy is detailed, who is admitted to the IESS Hospital with a presumptive diagnosis of threatened labor before 37 weeks of gestation due to contractile pain and slight uterine activity, but with the days presents clinical symptoms compatible with Covid-19 which is complicated by presenting base pathology. The treatment to be followed with respect to the use of certain medications at this stage is proposed considering that the patient is pregnant, with a base pathology in order to protect the maternal-fetal binomial.